ANALISIS STRATEGI ALFAMART DALAM EKSPANSI INDUSTRI RETAIL MODERN DI FILIPINA - Efendi, Difa Putra; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted to see the steps and strategies used by Alfamart in order to expand its modern retail in the Philippines. Alfamart is one of the retailers with product providers and trading companies that is very developed in Indonesia in the retail industry. This paper is qualitative research that uses Complexity and Global Expansion Strategy (CGES) theory which will look at the entry modes used by Alfamart to enter the Philippine’s retail market. In this research, researchers used the Individual - Group level of analysis. The Individual – Group level of behavioral analysis focuses on individuals who carry out international actions in groups. Data collection uses document analysis methods sourced from several books, journal articles and other references relevant to Alfamart's entry and development strategy in the Philippines. The research results show that Alfamart can expand and enter the Philippine’s retail market by using various strategies, where the selection and use of the right strategy is the main reason for the rapid development of Alfamart retail in the Philippines. The focus is on the entry mode of joint ventures and optimizing the global market complexity strategy that Alfamart uses in expansion, market observation and is supported by Philippine’s government regulations regarding the entry and exit of foreign investors. Keywords: Alfamart, Expansion, Joint Venture, Modern Retail.